The Effect of SGLT-2 Inhibitors on Serum Potassium and Serum Sodium Levels in Diabetic Patients taking SGLT-2 Inhibitors, Reporting in A Tertiary Care Hospital, Rawalpindi - Khattak, Abdul Latif; Rashid, Ahmar; Javed, Farah; Aziz, Sana; Siddiqi, Fuad Ahmad; Alihah, Syeda (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate how SGLT2 inhibitors, in comparison to a placebo and the maximum dose of Metformin, affect the levels of serum potassium and sodium in individuals with Type II Diabetes. Study Design: Quasi- Experimental study Place and Duration of Study: Department of Medicine (Endocrinology) in a tertiary care hospital, in Rawalpindi Pakistan from Oct 2022 to Mar 2023. Methodology: A total of 200 patients with type II diabetes were recruited and divided into two groups. 100 diabetic patients were placed in Group-A and were given SGLT-2 inhibitors (Dapagliflozin and Empagliflozin) while 100 diabetic patients were placed in Group-B, given a placebo in addition to a maximum dose of 2000mg/day of Metformin they were already taking. Patients were observed over 24 weeks and the levels of serum potassium and sodium were assessed at the end of this period. Results: Mean sodium levels of patients receiving SGLT-2 inhibitors were 139.3±3.18 mmol/L while of those who received placebo were 138.94±3.5 mmol/L with a p-value of 0.44. The mean potassium levels of patients who received SGLT-2 inhibitors were 3.96±0.33 mmol/L while of those who received placebo were 3.97±0.38 mmol/L with a p-value of 0.8. There was statistically no difference in serum sodium and potassium levels of the two groups. Conclusion: SGLT-2 inhibitors (Dapagliflozin and Empagliflozin) do not affect serum sodium and potassium levels when compared to patients who were given placebo as there was statistically no significant difference among the two groups.